Carbonised Agro-Waste Adsorbents for Automotive Lubricating Oil Removal - Harun, Hasnida; Nor Hazren Abdul Hamid; Nor Maizzaty Abdullah; Inawati Othman; Noor Hasyimah Rosman (Journal of Advanced Industrial Technology and Application, 2025)
The increasing generation of waste lubricating oil, driven by expanding industrial and automotive activity, poses a significant threat to aquatic ecosystems due to its persistence, hydrophobicity, and complex chemical composition. This study evaluates two abundant agro-waste residues: rice husk (RH) and sugarcane bagasse (SB) as potential adsorbents for lubricating oil removal. Both biomasses were pre-treated with 0.1 M NaOH to enhance surface porosity and hydrophobicity, followed by carbonisation at 550 °C. Three adsorbent formulations were prepared based on RH:SB weight ratios of 24:6, 15:15, and 6:24 g. Batch experiments were conducted at oil concentration of 25, 30, and 35 v/v% and contact times of 10, 20, and 30 min using a fixed 30g adsorbent dosage of RH and SB. The response behaviour was further examined using ANOVA and contour-plot analysis under Response Surface Methodology to interpret factor interactions and adsorption trends. All adsorbent mixtures demonstrated high removal efficiencies, achieving up to 100% oil removal, with the 15:15 g ratio showing the most consistent performance at 20 v/v% of oil concentration. FTIR analysis confirmed key lignocellulosic functional groups such as hydroxyl, carbonyl, methylene, aromatic structures which supporting the strong intermolecular interactions responsible for oil removal. Overall, the findings demonstrate that carbonised RH and SB are viable, low-cost, and environmentally sustainable adsorbents capable of efficiently removing used lubricating oil.